Challenges in Accessing Dental Care for Special Care Populations in Jazan, Saudi Arabia: A Study among Health Professionals and Caregivers - Najmuddin, Mohammed; Alhazmi, Yaser Ali; Saheb, Safeena Abdul Khader; Alfaifi, Wafa Hadi; Sori, Sara Abdulhamid; Faris, Shreefah M.; Chourasia, Hemant Ramesh; Porwal, Amit; Jethlia, Ankur; Mujoo, Sheetal; Wahajuddin, Mohammed (European journal of general dentistry, 2025)
Those with disabilities lack access to adequate dental health care services that are fundamental for maintaining their oral health. The study was primarily conducted to identify the actual barriers to dental care services for disabled patients. The study aimed to find the perfect solution capable of addressing the problems encountered by both dental practitioners and disabled patients. The present cross-sectional study was performed on 160 study subjects, 100 including parents and patients and 60 dental professionals including consultants, dental practitioners, interns, and dental undergraduate students, by using two self-administered structured questionnaires for both groups. The demographic variables and any information by parents and dental professionals that might be helpful in managing the treatment of disabled children were recorded. The data obtained was subjected to statistical analysis using IBM SPSS version 20.0 software. Note that 56.7% of the dental professionals who participated in the study were dental interns in the age group of 20 to 25 years belonging to the Saudi region. Majority of these dental professionals treated disabled children during their dental practice and even acquired specialized training for their management. While a majority of the hospitals comprise of renowned facilities for managing disabled children, right from parking facilities to wheelchairs, most of them lack special facilities like signboards, special toilets, adequate equipment, trained associates, pharmacy, etc. Most of the parents of these disabled children come from rural areas having only secondary education levels. A majority of the patients were physically disabled and suffered from dental problems, the most prevalent one being dental caries. Most parents discovered that the brushing methodology contributed to such dental problems. Few parents blamed the unavailability of equipment as a barrier to getting treated. Most parents were worried constantly over treatment costs and were fearful to get treated. Despite dental care provided to parents and caregivers of disabled individuals, it is our observation that the numbers are still inadequate in the Jazan region, Saudi Arabia. The most common barriers for this include treatment cost and the constant fear of getting the dental treatment done by a dental care provider.